2021
DOI: 10.1186/s12967-021-03056-1
|View full text |Cite
|
Sign up to set email alerts
|

UBE2T promotes autophagy via the p53/AMPK/mTOR signaling pathway in lung adenocarcinoma

Abstract: Background Ubiquitin-conjugating enzyme E2T (UBE2T) acts as an oncogene in various types of cancer. However, the mechanisms behind its oncogenic role remain unclear in lung cancer. This study aims to explore the function and clinical relevance of UBE2T in lung cancer. Methods Lentiviral vectors were used to mediate UBE2T depletion or overexpress UBE2T in lung cancer cells. CCK8 analysis and western blotting were performed to investigate the effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 39 publications
1
45
0
Order By: Relevance
“…Recently, UBE2T was reported to promote β-catenin nuclear translocation in HCC through the MAPK/ERK axis ( 40 ). In addition, UBE2T promotes the progression of LUAD by regulating autophagy through the p53/AMPK/mTOR signaling pathway ( 41 ). As a member of the E2 family, UBE2T enhances DNA crosslinking-induced damage repair by monoubiquitinating the FANCI-FANCD2 complex ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, UBE2T was reported to promote β-catenin nuclear translocation in HCC through the MAPK/ERK axis ( 40 ). In addition, UBE2T promotes the progression of LUAD by regulating autophagy through the p53/AMPK/mTOR signaling pathway ( 41 ). As a member of the E2 family, UBE2T enhances DNA crosslinking-induced damage repair by monoubiquitinating the FANCI-FANCD2 complex ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…8 LUAD is the main subtype of NSCLC. 9 Nevertheless, the function of hsa_circ_0000729 in NSCLC remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Using the same method, Shen and colleagues also developed reliable gene PGSs for LUSC and glioblastoma, respectively [ 31 ]. Moreover, our team previously reported that UBE2T promoted autophagy in NSCLC, and a signature of 18 UBE2T-related autophagy genes greatly enhanced the predictive accuracy of prognosis compared to the UBE2T gene alone [ 19 ]. Taken together, these results suggest that genes critical for cancer cell survival are refined candidate biomarkers for prognostic prediction.…”
Section: Discussionmentioning
confidence: 99%
“…The remaining survival genes were entered into a LASSO regression model, and genes with non-zero coefficients were used to establish a multi-gene survival model. The resulting LASSO coefficients and corresponding patient expression levels of each included gene were incorporated into a risk score algorithm to quantitatively evaluate patient risk as published previously [ 16 , 19 , 20 ]. To assess the predictive ability of the prognostic multiple gene models, time-dependent receiver operating characteristic (ROC) curves were plotted for the risk scores with the utilization of the R package survivalROC.…”
Section: Methodsmentioning
confidence: 99%